2011
DOI: 10.1002/jrs.3026
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing variability in in vivo Raman spectroscopic properties of different anatomical sites of normal tissue in the oral cavity

Abstract: Raman spectroscopy is an inelastic light scattering technique that is capable of probing biochemical and biomolecular structures and conformations of tissue. This study aims to characterize the in vivo Raman spectroscopic properties of different normal oral tissues in the fingerprint region (800-1800 cm −1 ) and to assess distinctive biochemical variations of different anatomical regions in the oral cavity. A specially designed fiber-optic Raman probe with a ball lens was utilized for real-time, in vivo Raman … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
56
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 39 publications
6
56
0
1
Order By: Relevance
“…Previous studies on¯nger-print and high wavenumber region have demonstrated that buccal and labial mucosa, keratinized or masticatory mucosa and specialized mucosa on the tongue can be classi¯ed as distinct clusters of subsites. [34][35][36] While some studies indicate that these subsite-anatomical di®erences confound the healthy and pathological discrimination, 37 other studies have stated that the inherent anatomical di®erences may not hinder healthy vs pathological classi¯cation. 47 In the present study, Raman spectroscopic di®erences between the three common subsites of oral cancer development in the Indian subcontinent-buccal mucosa, movable mucosa of the lip and tongue were evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on¯nger-print and high wavenumber region have demonstrated that buccal and labial mucosa, keratinized or masticatory mucosa and specialized mucosa on the tongue can be classi¯ed as distinct clusters of subsites. [34][35][36] While some studies indicate that these subsite-anatomical di®erences confound the healthy and pathological discrimination, 37 other studies have stated that the inherent anatomical di®erences may not hinder healthy vs pathological classi¯cation. 47 In the present study, Raman spectroscopic di®erences between the three common subsites of oral cancer development in the Indian subcontinent-buccal mucosa, movable mucosa of the lip and tongue were evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Three major RS studies in thē nger-print and high wavenumber region have also demonstrated di®erences arising due to epithelial and sub-epithelial structures, submucosa and degree of keratinization in subsites of healthy subjects and suggested clustering of sites based on anatomical and spectral similarities. [34][35][36] While the¯rst in vivo study by Guze et al suggested that spectra for di®erent oral sites within the same ethnic group are signi¯cantly di®erent and clearly separable, the consequent study by Bergholt et al divided major subsites into three di®erent clusters based on their histological and spectroscopic characteristics. The three groups included -(a) buccal mucosa, inner lip and soft palate, (b) dorsal, ventral tongue and°o or of mouth, (c) gingiva and hard palate.…”
Section: Introductionmentioning
confidence: 99%
“…Bergholt et al used a Raman fiber probe to study various locations within the oral cavity [426]. Short et al studied the gastrointestinal tract with Raman spectra in the high wavenumber region [427].…”
Section: Applicationsmentioning
confidence: 99%
“…Bergholt et al have shown that the measurement location can have a large effect on the acquired Raman signal [426]. Because Raman spectroscopy is fundamentally a point-based measurement technique, additional information is required to ensure that data is acquired from the correct location.…”
Section: Challengesmentioning
confidence: 99%
See 1 more Smart Citation